Effect of Ti content on the microstructure and mechanical properties of TiAlSiN nanocomposite coatings. (September 2016) - Ma, Quansheng; Li, Liuhe; Xu, Ye; Ma, Xuan; Xu, Yi; Liu, Hongtao
Abstract: TiAlSiN coatings has been proposed and studied because of their desirable properties in hardness and coating-substrate adhesion. Further improvement of their performance can be achieved by better understanding the effect of the concentration of each element on the microstructure and mechanical properties of the coatings. In this paper, the TiAlSiN coatings with different Ti content were deposited by reactive DC magnetron sputtering method. The microstructure and mechanical properties of the coatings were analyzed by energy dispersive spectroscopy, X-ray diffraction, transmission electron microscope, scanning electron microscope, nano-indentor and Rockwell indentation tester. The results reveal that TiAlSiN coatings consisted of amorphous phase and crystalline phase. With a Ti content of 63 at.%, as well as a Si content of 7 at.%, a super-hard TiAlSiN coating with a nanoindentation hardness of 66 GPa was achieved. What is more, in contrast to the well-described super-hard nanocomposite TiAlSiN coatings, another "nanocomposite" microstructure coating with a Ti content of 29 at.% in which the amorphous phase is wrapped in a crystalline phase was identified, with a comparatively low hardness value of 20 GPa. The highest adhesion strengths with a Rockwell indentation classes HF2 was achieved for a coating with a Ti content of 63 or 65 at.%. Highlights: A new mosaic target was used, and the coatings deposited by it were uniform. A TiAlSiN coating with the super-hardness of 66 GPa was attained. A "very soft" TiAlSiN coating with the microstructure of "amorphous phase wrapped in crystalline phase" was obtained.